Iranian Nursery School Teachers' Knowledge about Safety Measures in Earthquakes - Mahmoud Nekoei Moghadam; Shiva Shykhoeslami; Rohaneh Rahimisadeq; Narges Khanjani (Al Ameen Medical College, 2012)
Introduction: The occurrence of disasters and related casualties is one of the realities of man's life. Although man cannot prevent the incidence of many unfortunate events, but still can alleviate its consequences by applying safety measures. Children's health is the most important concern of parents and supervisors, and as this vulnerable group spends a lot of time in the nursery, their safety and protection at disasters and inside the nursery is one of the main health priorities. The main objective of this survey is to find out the level of nursery school teachers' awareness in Kerman, Iran; about safety measures in earthquakes. Methods: A cross sectional study was conducted. The study population was the nursery school teachers of Kerman. A sample of 239 teachers was enrolled through cluster sampling and each completed a questionnaire. Descriptive statistics, regression and chi-square were applied for data analysis. Results: The findings show that only 27.4% of the teachers had previously been through training and education about these safety measures. The majority (54.8%) of nursery teachers' awareness regarding earthquake was moderate and the majority's (62.3%) level of awareness regarding fire (resulting from earthquake) was moderate too. There was a significant relationship between attending previous training and the more knowledge. Conclusion: Kerman is a disaster prone province in Iran. One of the main threats is earthquake and fire that may happen afterwards. Therefore intense and frequent education of kindergarten teachers who spend almost half of the day with the vulnerable children is essential and has positive consequences on their knowledge